On Hadamard Product of Hypercomplex Numbers - Da¸sdemir, A. (KU Publ., 2021)
Certain product rules take various forms in the set of hypercomplex numbers. In this paper, we introduced a new multiplication form of the hypercomplex numbers that would be called ¾the Hadamard product¿, inspired by the analogous product in the real matrix space, and investigated some algebraic properties of that, including the norm of inequality. In particular, we extended our new definition and its applications to the complex matrix theory.
Гиперкомплексті сандар Адамардың көбейтіндісі туралы
О произведении Адамара гиперкомплексных чисел
Keywords: Quaternion product; dot product; Hadamard product; hypercomplex number